1996
DOI: 10.1037/0022-006x.64.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Attachment organization and history of suicidal behavior in clinical adolescents.

Abstract: One hundred thirty-three adolescents in psychiatric treatment participated in a case-comparison study investigating the association of attachment patterns with a history of suicidal behaviors. The comparison group comprised 64 adolescents who had never experienced suicidal ideation or behaviors; the case group included 69 adolescents with histories of suicidal behavior (n = 53) and severe suicidal ideation (n =16). Attachment patterns were assessed using the Adult Attachment Interview. In accordance with defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
4
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 22 publications
15
101
4
6
Order By: Relevance
“…However, as has been found in other adolescent samples (e.g. Adam et al, 1996;Rosenstein and Horowitz, 1996), males on average received significantly lower ratings on the preoccupied pattern t(114)=Ϫ3·60, p<0·001, and significantly higher ratings of dismissingness, t(114)=3·51, p<0·002 in comparison to their female counterparts.…”
Section: Sex Differences On Attachment and Suicidal Characteristics Imentioning
confidence: 69%
“…However, as has been found in other adolescent samples (e.g. Adam et al, 1996;Rosenstein and Horowitz, 1996), males on average received significantly lower ratings on the preoccupied pattern t(114)=Ϫ3·60, p<0·001, and significantly higher ratings of dismissingness, t(114)=3·51, p<0·002 in comparison to their female counterparts.…”
Section: Sex Differences On Attachment and Suicidal Characteristics Imentioning
confidence: 69%
“…In addition, suicidal adolescents are more likely to live in nonintact families compared with non-suicidal peers (De Wilde et al, 1992;Kienhorst et al, 1990;Paluszny et al, 1991). When young people do live with their parents, there may be poor attachment (Adam, 1994;Adam et al, 1996;Lessard & Moretti, 1998;Martin & Waite, 1994), parent -child confl ict (Asarnow, 1992;Brent et al, 1990;Meneese & Yutrzenka, 1990;Rubenstein et al, 1989), hostility (Kosky et al, 1986) and rejection (Fotti et al, 2006). Moreover, family confl icts are among the most commonly identifi ed precipitants to self-harm, based on adolescent self-report (Lowenstein, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for such greater vulnerability may be a predisposition for these conditions in the face of stress, negative affect, and interpersonal difficulties, as evidenced elsewhere [49][50][51] . Yet, the overlap between suicidal behavior and insecure attachment could be interpreted as result of failure to resolve attachment-related distress, leading to the emergence of depressive symptoms, negative models of the self and the others, and lack of future expectations 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Respondents choose statements that reflect how they have felt over the past 2 weeks. BDI-II scores range between 0 and 63; categorical depression ratings are "minimal" (0-13), "mild" (14)(15)(16)(17)(18)(19), "moderate" (20)(21)(22)(23)(24)(25)(26)(27)(28), and "severe" . The authors found, in their assessed clinical sample, a cut-off of 17 or greater with a 93% true-positive rate and a 18% false-positive rate.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation